2021
DOI: 10.1002/smll.202007523
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Combination of G‐C3N4 and CDs for Enhanced Photocatalytic Performance: A Review of Synthesis, Strategies, and Applications

Abstract: Recently, heterogeneous photocatalysts have achieved much interest on account of their great potential applications in resolving many tough energy and environmental troubles around the world through an ecologically sustainable way. Heterogeneous nanocomposites composed of graphitic carbon nitride (g-C 3 N 4 ) and carbon dots (CDs) possess broad spectrum absorption, appropriate electronic band structures, rapid carrier mobility, abundant reserves, excellent chemical stability, and facile synthesis methods, whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
45
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 103 publications
(52 citation statements)
references
References 182 publications
(438 reference statements)
0
45
0
Order By: Relevance
“…Besides, it is noted that appropriate electronic structures, rapid carriers mobility and outstanding chemical stability can be also achieved by the modulation of dimension. [192] Reproduced with permission. [190] Copyright 2019, Royal Society of Chemistry.…”
Section: Dimension Modulation Of Cocatalystsmentioning
confidence: 99%
“…Besides, it is noted that appropriate electronic structures, rapid carriers mobility and outstanding chemical stability can be also achieved by the modulation of dimension. [192] Reproduced with permission. [190] Copyright 2019, Royal Society of Chemistry.…”
Section: Dimension Modulation Of Cocatalystsmentioning
confidence: 99%
“…Indeed, studies have undoubtedly demonstrated the effectiveness of composites in improving the properties of CDs, enhancing their performances in various applications and expanding their application scope. 48,49…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, semiconductor photocatalysts have attracted increasing attention owing to their highly efficient effect in easing energy crisis and reducing environmental pollution. Recently, a large variety of semiconductor photocatalysts have been explored including TiO 2 [1,2] and SrTiO 3 [3] , etc., which were mainly active during ultraviolet range, and C 3 N 4 [4] , Cu 2 O, Co 3 O 4 [5] and CdS [6] , etc. that have highly visible activity.…”
Section: Introductionmentioning
confidence: 99%